2023
DOI: 10.1097/md.0000000000033863
|View full text |Cite
|
Sign up to set email alerts
|

How proximal femur fracture patients aged 65 and older fare in survival and cause of death 5+ years after surgery: A long-term follow-up

Abstract: Although the incidence of proximal femur fractures (PFFs) is increasing, few detailed reports on associated long-term outcomes and causes of death exist. We aimed to evaluate long-term outcomes and causes of death ≥5 years after surgical treatment of PFFs. This retrospective study included 123 patients (18 males, 105 females) with PFFs treated at our hospital between January 2014 and December 2016. Cases (median age: 90 [range, 65-106] years) comprised 38 femoral neck fractures (FNFs) and 85 intertrochanteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although there are very limited data regarding the long-term follow-up after pathologic hip fracture, likely due to the increased mortality rate [16], there are certain data within the geriatric hip fracture data literature. Hashimoto et al [21] demonstrated that the main causes of death for geriatric hip fractures were senility, aspiration pneumonia, bronchopneumonia, worsening heart failure, acute myocardial infarction, and abdominal aortic aneurysm. The leading cause of death within 1 year reported from that study was aspiration pneumonia and the leading cause of death after 1 year was senility.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are very limited data regarding the long-term follow-up after pathologic hip fracture, likely due to the increased mortality rate [16], there are certain data within the geriatric hip fracture data literature. Hashimoto et al [21] demonstrated that the main causes of death for geriatric hip fractures were senility, aspiration pneumonia, bronchopneumonia, worsening heart failure, acute myocardial infarction, and abdominal aortic aneurysm. The leading cause of death within 1 year reported from that study was aspiration pneumonia and the leading cause of death after 1 year was senility.…”
Section: Discussionmentioning
confidence: 99%